Nonlinear d’alembert equation in the pseudo-euclidean space R_2,n and its solutions - Yuryk, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate the nonlinear D’Alembert equation in the pseudo-Euclidean space R_2,n and construct new exact solutions containing arbitrary functions.